2018
DOI: 10.3390/met9010010
|View full text |Cite
|
Sign up to set email alerts
|

Grain Boundary Complexions and Phase Transformations in Al- and Cu-Based Alloys

Abstract: High-pressure torsion has been used to obtain the ultra-fine grained (UFG) state with a high specific area of grain boundaries (GBs) in Al-Zn, Al-Mg, Cu-Ag, Cu-Co, and Cu-Ni solid solutions with face-centered cubic (fcc) lattices. The UFG samples were heated in a differential scanning calorimeter (DSC). Small endothermic peaks in the DSC curves were observed in the one-phase solid-solution area of the respective phase diagrams, i.e., far away from the bulk solidus and solvus lines. A possible explanation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 216 publications
(383 reference statements)
0
2
0
Order By: Relevance
“…Recently, the authors studied the samples of the Al–10 wt% Mg alloy in the single‐phase region of AlMg phase diagram after SPD by high‐pressure torsion (HPT). [ 39 ] In this work, it was shown that such compounds as metastable phases appear after HPT in the single‐phase region of the (Al) solid solution. On the contrary, other authors [ 40–43 ] found the metastable phases in the single‐phase region of AlMg alloys.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, the authors studied the samples of the Al–10 wt% Mg alloy in the single‐phase region of AlMg phase diagram after SPD by high‐pressure torsion (HPT). [ 39 ] In this work, it was shown that such compounds as metastable phases appear after HPT in the single‐phase region of the (Al) solid solution. On the contrary, other authors [ 40–43 ] found the metastable phases in the single‐phase region of AlMg alloys.…”
Section: Introductionmentioning
confidence: 98%
“…It is commonly believed that such broad segregations may belong to a special so-called non-equilibrium structure of a GB [2,3]. Other mechanism of the formation of such broad enriched regions is recently discussed in connection with the segregation induced GB structural transitions [14,[26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%